THE EFFECT OF ENHANCED RECOVERY AFTER BARIATRIC SURGERY (ERABS) PROTOCOL ON UNSELECTED COHORT OF ONE ANASTOMOSIS GASTRIC BYPASS (OAGB) PATIENTS Enhanced recovery in bariatric surgery - Aktimur, R.; Kirkil, C.; Yildirim, K.; Korkmaz, M. F. (Springer, 2017)
[Abstract Not Available]